Analysing and managing risks of bank lending - Onyiriuba, Leo (Lagos : Malthouse Press, NFS data bureau limited, 2008)
The book satisfies the need for effective management of lending risks as a survival strtegy for banks. It provides solutions to plug loopholes in lending practices and decisions, avert bank failures with sound credit policy, analysis and management.
Includes bibliographical references and index.
oif 05/06/14
Loan
Keywords: Bank loans; Risk management; Lending - banking; Nigeria